Analisis Dan Perancangan Sistem Informasi Alumni (Tracer Study) Berbasis Web Pada Sekolah Tinggi Ilmu Tarbiyah (Stit) Darul ‘Ulum Sarolangun - Hidayat, Husni; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
At this time STIT Darul ‘Ulum Sarolangun is processing data studio that handles alumni. still donemanually, by conducting conditional data collection at certain times and people, presentation of alumnidata that has not been computerized (not yet using information systems). The difficulty is when facingaccreditation of institutions and study programs, during the study program evaluation process, whendoing stake holders need staff, the student administration has difficulty in searching for data of studentswho have graduated among how many alumni, gender, GPA and average score, lowest and highest,already working or not. The purpose of this research is to analyze and study the problems of alumniinformation systems at STIT Darul ‘Ulum Sarolangun and produce a prototype of alumni informationsystems at STIT Darul‘ Ulum Sarolangun. The system design in this study uses UML tools (UnifiedModelling Languange) seperti use case, activity diagram, dan class diagram. Whereas in making aprototype system using MySQL tools to design a database and Adobe Dreamweaver CS6 to design aprototype system. This research produces a prototype of alumni information system that can managealumni data, tracking study data, news data, job data, scholarship data, donation data, activity data,computerized gallery data and can present the required alumni reports. It is expected that with acomputerized alumni information system, it can produce alumni information to make it easier foruniversities to know their alumni, as well as to produce more up to date alumni data information, theprototype of this alumni information system needs to be developed, so it can really be used online and canbe applied. In developing the prototype of this information system, it has not yet paid attention to theissue of data security (security), so for that further research can be supplemented by its data security system.